For a sound fiscal policy: Enabling public investment - Hubertus Bardt; Sebastian Dullien; Michael Hüther; Katja Rietzler (Institut der deutschen Wirtschaft (IW), 2020)
Public investment has been badly neglected in Germany over the past two decades, with the result that the public capital stock no longer meets the standards of a modern economy and is inadequate for the challenges that will be posed by demographic change and Germany's international decarbonisation commitments. In total, the areas of education, transport, communication networks and decarbonisation will require at least an additional exteuro450 billion of public investment or public investment subsidies over the next 10 years, equivalent to approximately exteuro45 billion a year. While this amount is manageable in overall economic terms, it is unrealistic to suggest that the required investment can be financed entirely through the reallocation of existing funds within the budget. Consequently, the German Constitution's debt rules should be supplemented by a Golden Rule allowing for borrowing equivalent to the value of the net investment. The leeway offered by mechanisms such as off-budget entities should be utilised until such a rule has been implemented. A sustained reduction in local government debt will also be important in view of the key role played by the municipalities in public investment, especially in transport infrastructure.
Keywords: H54; H60; 330; Infrastrukturinvestition; Investitionspolitik; Haushaltskonsolidierung; Reform; Deutschland